Review of liver injury associated with dietary supplements - Stickel, Felix; Kessebohm, Kerstin; Weimann, Rosemarie; Seitz, Helmut K. (Liver international, 2011)
Dietary supplements (DS) are easily available and increasingly used, and adverse hepatic reactions have been reported following their intake. To critically review the literature on liver injury because of DSs, delineating patterns and mechanisms of injury and to increase the awareness towards this cause of acute and chronic liver damage. Studies and case reports on liver injury specifically because of DSs published between 1990 and 2010 were searched in the PubMed and EMBASE data bases using the terms ‘dietary/nutritional supplements’, ‘adverse hepatic reactions’, ‘liver injury’; ‘hepatitis’, ‘liver failure’, ‘vitamin A’ and ‘retinoids’, and reviewed for yet unidentified publications. Significant liver injury was reported after intake of Herbalife® and Hydroxycut products, tea extracts from Camellia sinensis, products containing usnic acid and high contents of vitamin A, anabolic steroids and others. No uniform pattern of hepatotoxicity has been identified and severity may range from asymptomatic elevations of serum liver enzymes to hepatic failure and death. Exact estimates on how frequent adverse hepatic reactions occur as a result of DSs cannot be provided. Liver injury from DSs mimicking other liver diseases is increasingly recognized. Measures to reduce risk include tighter regulation of their production and distribution and increased awareness of users and professionals of the potential risks.